Temporal trends and mortality of post-ERCP pancreatitis in the United States: a nationwide analysis - Mutneja, Hemant Raj; Vohra, Ishaan; Go, Andrew; Bhurwal, Abhishek; Katiyar, Vatsala; Palomera Tejeda, Emmanuel; Thapa Chhetri, Kapil; Baig, Muhammad Arslan; Arora, Shilpa; Attar, Bashar (Endoscopy, 2020)
Background Post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP) is the most common and most serious complication of ERCP. Our aim was to estimate the nationwide incidence, temporal trends, and mortality of PEP in the United States and to establish risk factors associated with PEP development.Methods This was a retrospective cohort study analyzing Nationwide Inpatient Sample data from 2011 to 2017 using International Classification of Diseases codes. The primary outcomes were trends in PEP incidence and predictors of PEP development. Secondary outcomes were in-hospital mortality, length of hospital stay, and admission to the intensive care unit.Results Of 1 222 467 adult patients who underwent inpatient ERCP during the study period, 55 225 (4.5 %) developed PEP. The hospital admission rate of PEP increased by 15.3 %, from 7735 in 2011 to 8920 in 2017 (odds ratio [OR] 1.23, 95 % confidence interval [CI] 1.04 – 1.46; P = 0.02). The overall rate of mortality increased from 2.8 % of PEP cases in 2011 to 4.4 % in 2017 (OR 1.62, 95 %CI 1.10 – 2.38; P = 0.01). Multiple patient-related (alcohol use, cocaine use, obesity, chronic kidney disease, heart failure), procedure-related (therapeutic ERCP, sphincterotomy, pancreatic duct stent placement, sphincter of Oddi dysfunction), and hospital-related (teaching hospitals, hospitals located in the West and Midwest) factors that impact the occurrence of PEP were identified.Conclusions Our study showed rising hospital admission and mortality rates associated with PEP in the United States. This calls for a greater recognition of this life-threatening complication and amelioration of its risk factors, whenever possible.